Pengaruh Media Sosial WhatsApp Terhadap Pengelolaan Konflik Di Sekolah SMA Santo Thomas 2 Medan: Dampak Penggunaan WhatsApp terhadap Strategi Penyelesaian Konflik di SMA Santo Thomas 2 Medan - Sinurat, Lediana; Sitanggang, Nathanael; Simaremare, Aman (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to find and analyze the influence of WhatsApp social media on conflict management at SMA Santo Thomas 2 Medan. This study uses a quantitative approach with a descriptive design to describe the relationship between WhatsApp use and conflict dynamics between students. Data were collected through closed questionnaires distributed to 60 grade X students selected using stratified random sampling techniques. The research instrument has been tested for validity and reliability to ensure measurement accuracy. The results of the analysis show that there is a significant influence of WhatsApp use and conflict management, with a contribution of 33% to the variation in conflict management in schools. In conclusion, WhatsApp can play a positive role in helping communication and accelerating conflict resolution if used wisely. These findings are expected to be a reference for schools in managing social media to create a healthy communication environment.